2020
DOI: 10.1002/ijc.33032
|View full text |Cite
|
Sign up to set email alerts
|

Genetic polymorphisms in the cag pathogenicity island of Helicobacter pylori and risk of stomach cancer and high‐grade premalignant gastric lesions

Abstract: Helicobacter pylori (Hp) infects the stomach of about half of the human population and is strongly associated with the risk of gastric cancer (GC) and its premalignant precursors. The cag pathogenicity island (cagPAI) is a region of the Hp genome encoding for key molecular machinery involved in the infection process. Following a sequencing study, we selected 50 genetic polymorphisms located in seven cagPAI genes and tested their associations with the risk of advanced gastric premalignant lesions and GC in 1220… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 46 publications
0
14
0
Order By: Relevance
“…It has been established that the highly virulent H. pylori strains comprise the cytotoxin-associated genes pathogenicity island (CagPAI), which is a 40 kb region containing 31 genes encoding the elements of a type IV secretion system, participating in CagA toxic activity and following a series of in ammatory responses [10] . Research has shown that infections with CagA positive strains are more virulent than the strains without this genotype in gastric colonization and proliferation [11] . In the process of infection, CagA is localized on the plasma membrane, in which it is phosphorylated at speci c Glu-Pro-Ile-Tyr-Ala (EPIYA)-motifs through Src and Abl kinases in host [12,13] .…”
Section: Discussionmentioning
confidence: 99%
“…It has been established that the highly virulent H. pylori strains comprise the cytotoxin-associated genes pathogenicity island (CagPAI), which is a 40 kb region containing 31 genes encoding the elements of a type IV secretion system, participating in CagA toxic activity and following a series of in ammatory responses [10] . Research has shown that infections with CagA positive strains are more virulent than the strains without this genotype in gastric colonization and proliferation [11] . In the process of infection, CagA is localized on the plasma membrane, in which it is phosphorylated at speci c Glu-Pro-Ile-Tyr-Ala (EPIYA)-motifs through Src and Abl kinases in host [12,13] .…”
Section: Discussionmentioning
confidence: 99%
“…The study populations, histopathological and epidemiological parameters, and Hp cagPAI variant selection and genotyping procedures have been published previously (Canzian et al, 2020). Briefly, the study samples consisted of 1220 subjects from four LatAm countries (Venezuela, Colombia, Mexico and Paraguay) who were infected with cagA-positive Hp, including 150 GC, 177 high-grade premalignant lesions [HGPMLs, consisting of intestinal metaplasia (IM) types 2 and 3, and dysplasia] and 893 low-grade premalignant lesions (consisting of chronic or atrophic gastritis and IM type 1).…”
Section: Methodsmentioning
confidence: 99%
“…Cag A gene is part of the cytotoxin-associated gene pathogenicity island (cagPAI), which also contains the bacterial type IV secretion system (T4SS) whereby Cag A enters the gastric mucosal cells [24]. The presence of cagPAI seems to be associated with more severe gastric pathology, including gastric cancer [19], and some polymorphisms may also have a higher risk [25]. After having penetrated the epithelial cell membrane, Cag A is phosphorylated, and phosphorylated Cag A then interacts with different proteins causing damage to the infected cell [19].…”
Section: Cytotoxin-associated Gene a (Cag A)mentioning
confidence: 99%